2001
DOI: 10.1590/s0101-81752001000200021
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de Eurytrema coelomaticum (Giard & Billet) (Digenea, Dicrocoeliidae) em Bradybaena similaris (Férussac) (Gastropoda, Xanthonychidae)

Abstract: ABSTRACT. Development of ElIrylrellla coel omaliclIlII (Giard & Billet) (Digenea, Dicrococliidac) in Brat/ybaella silllilaris (Férussac) (Gastropoda, Xanthonychidae). To follow the larval development of Ewytrema coelomaliclIm (Giard & Billel, 1892) in 8radybaena similaris (Férussac, 1821) snails were separaled in three classes llsing lhe shell diameter: Class A (14.5-10 .2 mm), Class B (10.1-6.9 mm) and Class C (6.8-2.6 mm). Only snails belonging to classes A and B acquired the inteclion.Specimens of E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…in Brazil have been based on morphological characterization (TRAVASSOS et al, 1969;YAMAMURA et al, 1995;PINHEIRO et al, 2012), biological cycle (BRANDOLINI; AMATO, 2001), epidemiological trends (AZEVEDO et al, 2004;BASSANI et al, 2006), and pathological manifestations (YAMAMURA et al, 1995;HEADLEY, 2000;HEADLEY et al, 2009). Additionally, there are also descriptions of Eurytrema spp.…”
Section: Introductionmentioning
confidence: 99%
“…in Brazil have been based on morphological characterization (TRAVASSOS et al, 1969;YAMAMURA et al, 1995;PINHEIRO et al, 2012), biological cycle (BRANDOLINI; AMATO, 2001), epidemiological trends (AZEVEDO et al, 2004;BASSANI et al, 2006), and pathological manifestations (YAMAMURA et al, 1995;HEADLEY, 2000;HEADLEY et al, 2009). Additionally, there are also descriptions of Eurytrema spp.…”
Section: Introductionmentioning
confidence: 99%
“…In field research, snails were found close to the pastures, along with grasshoppers, which are intermediate hosts of this fluke. Their infection was confirmed by histological studies, as previously performed by Brandolini and Amato (2001), who described Eurytrema sporocysts in the Bradybaena digestive tract.…”
Section: /6mentioning
confidence: 65%
“…In the literature, there is no description of estimates of total number of eggs present in the uterus of E. coelomaticum . There are studies that evaluated the oviposture rate of the parasite in vitro , and these studies observed a deposition ranging from 194 to 746 eggs per day in different physiological solutions (Yamamura, 1989; Brandolini and Amato, 2001). According to Bassani et al (2007) the proportion of eggs eliminated and observed via EPG is not directly related to number of parasites in the host, even considering those who lay their eggs directly in lumen of intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Yamamura (1989) analyzing the oviposture of E. coelomaticum ( in vitro ) observed an average daily of 641 eggs. Brandolini and Amato (2001) testing different physiological media observed that Locke solution presented the best oviposture rate with an average of 746 ± 139 eggs, followed by Earle solution with 304.6 ± 154.7 and finally the saline solution to 0.85 % with 194.5 ± 132 eggs. About this information, there are no records in the literature of estimate number of eggs present in the uterus of E. coelomaticum .…”
Section: Introductionmentioning
confidence: 99%